Formation and Adaptation of the Sugar Cartel in Austria-Hungary - Nikolaus Fink (Austrian Institute of Economic Research (WIFO), 2016)
This paper studies the legal sugar cartel in Austria-Hungary in 1891-1914. I analyse the cartel formation prior to 1891 that was enabled by an excise tax. The cartel started with simple annual quotas and - despite breakdowns - learned to adapt to inventory demand, entry, internal coordination problems and lowered import protection. Detailed qualitative evidence on the inner workings and prices, opportunity costs and sales data on a monthly basis are discussed. The success of the cartel at subsequent stages is evaluated.
Keywords: 330; Cartels; Collusion; Sugar Industry; Storage